Isolation of Tahyna virus from biting midges (Diptera, Ceratopogonidae) in Czecho-Slovakia - Halouzka, J; Pejcoch, M; Hubálek, Z; Knoz, J (Acta virologica, 1991)
A total of 14,250 haematophagous biting midges (genus Culicoides, Diptera: Ceratopogonidae) were collected in June 1986 in the mountains Ceskomoravská vysocina (about 600 m above sea level); from these 2 strains of Tahyna virus (serogroup California, Bunyaviridae) were isolated. To our knowledge this is the first isolation of a California serogroup virus from the species of family Ceratopogonidae as well as the first report of arbovirus isolation from biting midges in Europe.
Keywords: Ceratopogonidae; myši; viry kalifornské encefalitidy; Insect Vectors; Vero Cells; Czechoslovakia; Animals; Mice; Encephalitis Virus, California; hmyz - vektory; Vero buňky; zvířata; Československo